Pengaruh Penambahan Kulit Buah Naga Dan Jahe Terhadap Kandungan Antioksidan Permen Jeli - Maria Angelina Diah Anggraheni (Fakultas Pertanian, 2025)
. Dragon fruit is one type of tropical fruit that is being developed in Indonesia. Some of the ingredients in the dragon fruit peels and ginger act as antioxidants that are good for human health. Dragon fruit peels contain betacyanin and vitamin C. While ginger contains oleoresin and vitamin C. The optimize of utilization of dragon fruit peels and ginger are to add the jelly candy production. The study design was a Randomized Block Design (RBD) with 2 factors and 3 levels on each factor. The first factor is 0 ml, 10 ml and 30 ml dragon fruit peels. The second factor is ginger 0 ml, 37.50 ml and 41.50 ml. Observation variables consisted of water content, color (L *, a *, b *), vitamin C, betacyanin, antioxidants, antioxidant compound, organoleptic (color, taste, aroma, and texture). The results of this study showed that the selected treatment was the jelly candy added with 30 ml dragon fruit peel and 41.50 ml ginger. This jelly candy had a moisture content of 13.75%, brightness of 31.30, red color of 2.70, yellow color of 2.60, vitamin C of 2.01%, betacyanin of 61 , 39 mg / l, and antioxidant activity of 37.98%. In jelly candies with selected treatments contained antioxidant compound in the form as Diisooctyl Phthalate compounds and 1,2 - Benzenedicarboxylic Acid - 1,2 - Benzenedicarboxylic Acid, Bis (2-Ethylhexyl) Esters - Benze.